Dielecric Relaxation in Energy Condensed Systems on the Basis of Polyefirretane Elastomer. II. Temperature Dependence and Ignition; Combustion, Explosion and Shock Waves; Vol. 55, No. 2 - Sadovnichy D. N. Dmitry Nikolaevich; Milyokhin Yu. M. Yury Mikhaylovich; Lopatkin S. A. Sergey Anatolyevich; Lopatkina (Lopatkina) T. S. Tatjyana Sergeevna; Malinin S. A. Sergey Aleksandrovich; Gross I. N. Irina Nikolayevna (2019, 2019)
Title screen